Faktor-Faktor Yang Mempengarui Hasil Belajar Peserta Didik (Literature Review) - Yandi, Andri; Nathania Kani Putri, Anya; Syaza Kani Putri, Yumna (Siber Nusantara Publisher, 2023)
Abstract: Literature articles reviewing the factors that influence student learning outcomes are scientific articles that aim to build research hypotheses about the influence of variables to be used in further research, within the scope of education. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) The use of learning resources affects learning outcomes; 2) The school environment influences learning outcomes; and 3) School culture influences learning outcomes. Apart from these 3 exogenous variables, there are many other factors which influence learning outcomes including learning motivation, teacher competence, teacher communication, study discipline, classroom management, organizational climate, and self-management. Abstrak: Artikel literatur review faktor-faktor yang mempengaruhi hasil belajar peserta didik adalah artikel ilmiah yang bertujuan membangun hipotesis riset pengaruh antar variabel yang akan digunakan pada riset selanjutnya, dalam ruang lingkup ilmu pendidikan. Metode penulisan artikel Literature Review ini adalah dengan metode library risearch, yang bersumber dari media online seperti Google Scholar, Mendeley dan media online akademik lainnya. Hasil artikel Literature Review ini adalah bahwa: 1) Pemanfaatan sumber belajar berpengaruh terhadap hasil belajar; 2) Lingkungan sekolah berpengaruh terhadap hasil belajar; dan 3) Budaya sekolah berpengaruh terhadap hasil belajar. Selain dari 3 variabel exogen ini, masih banyak faktor lain di antaranya yang mempengaruhi hasil belajar diantaranya yaitu motivasi belajar, kompetensi guru, komunikasi guru, disiplin belajar, pengelolaan kelas, iklim organisasi, serta manajemen diri.